Singing from the Same Hymn Sheet? A Semantic and Convergence Analysis of the Extent to Which ‘Smart’ is Similarly Understood and Applied Across Energy, Transport, and Waste Management Sectors of Urban Planning - Onyango, Vincent; Forghaniallahabadi, Maryam; Gazzola, Paola (European Scientific Journal, ESJ, 2025)
The term ‘smart’ is widely used in urban planning, and it is often linked to the use and adoption of technologies or cost-efficiency measures in support of urban development and management. Whether the term is consistently understood and applied to inform practice across different policy sectors is unclear. This paper explores the understandings and applications of the term ‘smart’ within energy, transport, and waste management sectors of urban planning. A systematic literature review, guided by PRISMA criteria, was conducted, and NVivo-based coding was used to assess convergence. The findings provide a comprehensive profile of the term’s convergent and differential understandings and reflect on the scope for standardized terminology for ‘smart’ in urban planning. The term broadly describes a means of ‘deploying mechanical solutions’ pursuing efficiency and optimization, rather than ‘transformational outcomes’ e.g. sustainability. Thus, meaning and different eco-modernism goals are pursued in each sector, steeped in a language of technology-based paradigm, but hollow in meeting any fundamental transformation of the status quo. We conclude that while the concept of ‘smart’ can be adapted to different socio-economic and regional contexts, it requires a shared theoretical foundation. Future research could explore whether differences in understanding and application may be observed at regional levels.